Hubungan antara Motif Penggunaan Fitur LINE Today dan Interaktivitas Khalayak dengan Kepuasan Khalayak Menggunakan Fitur LINE Today - Aprida Mulya, Resti; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2018)
The research was aimed to determine the relationship between motive and audience interactivitywith the gratification obtained from using LINE Today feature. Based on the hypothesis conductedusing data Pearson correlation analysis dan Kendall Tau correlations analysis. The resultsshowed that there was a positive correlation between motive and gratification obtained from usingLINE Today feature starter with significance value 0,000 (<0,01). Furthermore, Kendall Taucorrelation test of audience interactivity and gratification obtained using LINE Today featureshowed a positive relationship with significance value of 0.003 (<0.005) and correlation value of0,347. This means that the more motive and the more audience interactivity then gratificationobtained will be higher.